P643 Psoriasis induced by anti-TNF therapy in Inflammatory Bowel Disease: analysis of therapeutic management and evolution of both diseases in a nationwide cohort study. (30th January 2023) - Sanz Segura, P; Gomollón, F; García García, S; Vela, M; Fernández-Clotet, A; Muñoz, R; García de la Filia, I; García Prada, M; Ferrer Rosique, J A; García, M J; de Francisco, R; Arias, L; et al.
Abstract: Background: Some patients with Inflammatory Bowel Disease (IBD) who are treated with anti-TNFα therapy develop a drug-induced psoriasis (IP) as an adverse event. There are some therapeutic approaches, being more frequent to change the biologic therapy to ustekinumab, effective and approved for the treatment of both entities. This could be the best option, but available data are lacking and it could increase the risk of IBD relapse. Our aim is to assess the management of anti-TNF IP in IBD, and the subsequent evolution of both diseases in a large nationwide cohort of patients. Methods: Retrospective, observational multicenter study from the prospectively maintained Spanish ENEIDA registry. Participants were patients with IBD and anti-TNFα IP. At baseline, psoriasis severity was classified as mild, moderate or severe, and remission was defined as the resolution of skin lesions, clinical response as an improvement without complete resolution, and no response as the absence of improvement. IBD clinical activity was defined based on Harvey-Bradshaw Index and Partial Mayo Score. All items were evaluated when available at baseline and 16, 32 and 54 weeks. Results: Anti-TNFα IP was reported in 234 patients (CD: 185, UC: 46, unclassified IBD: 3). SWAP strategy was chosen in 76 patients (32.5%), most of them to ustekinumab (90.8%), 71 (30.3%) patients continued anti-TNF, 49 (20.9%) discontinued it, and in 38 (16.2%) a switch to a second anti-TNF was made. The decision to continue or not anti-TNF was associated to psoriasis severity (p<0.001) and baseline IBD activity (p=0.03). In mild psoriasis, anti-TNF was continued in 56.81% of patients, whereas SWAP and withdrawal of the anti-TNF were the most used in moderate and severe disease (32.3% and 36.5% respectively). SWAP strategy was also the most used in active IBD (46%). During follow-up, CD activity got worse in anti-TNF withdrawal group (p=0.003), without differences in the other groups. Regarding to psoriatic lesions, all strategies showed a significant improvement, with worse results when anti-TNF was continued (remission rate of 58%, p=0.042), and without differences between the other strategies at week 54. In multivariate analysis, male gender was associated with IBD remission (HR 0.233; IC95% 0.061-0.894). Trunk (OR 2.777; IC95% 1.120-6.889), as well as palms and soles location (OR 2.091; IC95% 1.018-4.294), and stopping anti-TNF treatment (OR 3.010; IC95% 1.110-8.159), were independently associated with remission of skin lesions. Conclusion: Evaluating IBD activity and psoriasis severity is essential before modifying IBD treatment due to IP. Continuing anti-TNF treatment in mild psoriasis cases, and considering SWAP to ustekinumab in moderate-severe ones, could be a suitable strategy.